Phytochemical Screening and In Vitro Anti-Inflammatory Activity through Protein Denaturation Inhibition of Tigarun (Crataeva nurvala Buch. -Ham.) Stem Bark - Fadlilaturrahmah Fadlilaturrahmah; Mia Fitriana; Alya Hanifa; Resa Amalia Syabana (Sanata Dharma University, 2026)
Crataeva nurvala Buch. -Ham. is a medicinal plant commonly found in South Kalimantan, Indonesia. This study aimed to identify the phytochemical constituents and evaluate the in vitro anti-inflammatory activity of the stem bark extract of C. nurvala. The stem bark was extracted by maceration using ethanol and then fractionated by liquid-liquid partition with n-hexane, ethyl acetate, and n-butanol. Phytochemical screening was conducted using standard tube tests. The in vitro anti-inflammatory activity was assessed by measuring the inhibition of protein denaturation using Bovine Serum Albumin (BSA), and the IC₅₀ values were calculated. Phytochemical analysis revealed that the ethanol extract and the ethyl acetate fraction contained alkaloids, flavonoids, triterpenoids, phenols, and tannins. The n-hexane fraction showed the presence of triterpenoids, while the n-butanol fraction contained flavonoids. The IC₅₀ values of the ethanol extract, n-hexane, ethyl acetate, and n-butanol fractions were 122.07 ppm, 55.72 ppm, 96.01 ppm, and 155.88 ppm, respectively. Diclofenac sodium, used as a reference, showed an IC₅₀ of 59.79 ppm. These results indicate that the n-hexane fraction of C. nurvala stem bark possesses the strongest in vitro anti-inflammatory activity among the tested samples.